2016
DOI: 10.1038/srep38695
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dextromethorphan on MDMA-induced serotonergic aberration in the brains of non-human primates using [123I]-ADAM/SPECT

Abstract: 3,4-Methylenedioxymethamphetamine (MDMA), a common recreational drug, is known to cause serotonergic neurotoxicity in the brain. Dextromethorphan (DM) is a widely used antitussive reported to exert anti-inflammatory effect in vivo. In this study, we examined the long-term effect of MDMA on the primate serotonergic system and the protective property of DM against MDMA-induced serotonergic abnormality using single photon emission computed tomography (SPECT). Nine monkeys (Macaca cyclopis) were divided into three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 57 publications
3
14
0
Order By: Relevance
“…Using a selective SERT PET radiotracer, we monitored a long-term SERT occupancy/recovery in vivo and evaluated the AMI neuroprotection after MDMA induction. Our results showed that acute and repeated administration of MDMA signi cantly induced SERT reduction levels in all regions at day 14 compared to the controls, which were supported by previous studies, revealing that the effect of MDMA on SERT binding was a robust nding in rodents [13,20,42,43,44]. Those reports indicate that the effect of MDMA on SERT binding is a robust nding in rodent.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Using a selective SERT PET radiotracer, we monitored a long-term SERT occupancy/recovery in vivo and evaluated the AMI neuroprotection after MDMA induction. Our results showed that acute and repeated administration of MDMA signi cantly induced SERT reduction levels in all regions at day 14 compared to the controls, which were supported by previous studies, revealing that the effect of MDMA on SERT binding was a robust nding in rodents [13,20,42,43,44]. Those reports indicate that the effect of MDMA on SERT binding is a robust nding in rodent.…”
Section: Discussionsupporting
confidence: 91%
“…However, it decreased in cortical regions [49]. Ma et al, (2016) reported that the SERT recovery rate was on average of ~ 66.6% and ~ 68.6% after MDMA administration in the striatum, thalamus, and midbrain at 24 and 54 months, respectively [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the potential treatments to protect toxicity caused by MDMA have also been studied. Dextromethorphan and its metabolite, dextrorphan, may have a protective effect against MDMA-induced serotonergic toxicity in the brain (Finnegan, Skratt, Irwin, & Langston, 1989;Ma et al, 2016). Dextrorphan was believed to prevent the effects of serotonin depletion by MDMA in the striatum, hippocampus, and cortex (Finnegan et al, 1989).…”
Section: Previous Studies On the Therapeutic Targets For Mdma Toxicitymentioning
confidence: 99%